Children without language : from dysphasia to autism - Danon-Boileau, Laurent, 1946- (Oxford University Press, 2006)
Communication and language disorders are often considered from one particular point of view - either psychological or neurological. Danon-Boileau argues that this is a serious mistake. He emphasizes that a child's trouble can stem from a variety of causes: neurological problems similar to those of aphasia, cognitive impairments, and psychological disorders, and, thus, the interaction of these elements needs to be taken into account. In precise case studies, Danon-Boileau describes the situations he has confronted and traces the causes of changes in the child when they happen. Combining linguistic, cognitive, and psycho-analytic approaches, "Children without Language" provides a unique perspective on speech and communication disorders in children and will be an essential volume for speech therapists, developmental psychologists, linguistics scholars and anyone wishing to reflect seriously on why we speak and how communication occurs